Tfl deletion induces extraordinary Cxcl13 secretion and cachexia in VavP-Bcl2 transgenic mice - Minagawa, Kentaro; Wakahashi, Kanako; Fukui, Chie; Kawano, Yuko; Kawano, Hiroki; Suzuki, Tomohide; Ishii, Shinichi; Sada, Akiko; Nishikawa, Shinichiro; Asada, Noboru; Katayama, Yoshio; Matsui, Toshimitsu (Frontiers in Immunology, 2023)
Follicular lymphoma (FL) are associated with overexpressed BCL-2 and other genetic aberrations, including 6q-. We identified a novel gene on 6q25, “Transformed follicular lymphoma (TFL),” from a transformed FL. TFL regulates several cytokines via mRNA degradation, which has been suggested to underlie resolving inflammation. Fluorescence in situ hybridization revealed a deletion of TFL occurred in 12.8% of various B-cell lymphoma samples. We developed VavP-bcl2 transgenic, TFL deficit mice (Bcl2-Tg/TFL-/-) to seek how TFL affects disease progression in this lymphoma model. While Bcl2-Tg mice developed lymphadenopathy and died around 50 weeks, Bcl2-Tg/TFL-/- mice lost body weight around 30 weeks and died about 20 weeks earlier than Bcl2-Tg mice. Furthermore, we found a unique B220- IgM+ cell population in the bone marrow of Bcl2-Tg mice. cDNA array in this population revealed that CXCL-13 mRNA in Bcl2-Tg/TFL-/- mice expressed significantly higher than Bcl2-Tg mice. In addition, bone marrow extracellular fluid and serum showed an extremely high CXCL-13 concentration in Bcl2- Tg/TFL-/- mice. Among bone marrow cells, the B220- IgM+ fraction was the main producer of CXCL-13 in culture. A reporter assay demonstrated TFL regulates CXCL-13 via induction of 3'UTR mRNA degradation in B lineage cells. These data suggest TFL regulates CXCL-13 in B220- IgM+ cells in the bone marrow, and a very high concentration of serum CXCL-13 arising from these cells may contribute to early death in lymphoma-bearing mice. Since several reports have suggested the association of CXCL-13 expression with lymphoma, these findings provide new insights into cytokine regulation via TFL in lymphoma.